Effect of Cognitive-Behavioral Therapy and Emotion Regulation Therapy on the General Health, Aggression, and Job Stress of Nurses - Simin Farhangian; Zeinab Mihandust; Vahid Ahmadi (Hamadan University of Medical Sciences, 2022)
Background and Objective: One of the factors affecting the mental health of people is their job. Nursing is a source of stress due to the stress in its nature. Although the common goal of all psychotherapy approaches is to promote mental health, the results of studies have shown that there is a significant difference between them in terms of effectiveness. Therefore, the selection of the best psychological treatment to promote nurses' mental health has always been important. Materials and Methods: In this quasi-experimental study, 45 nurses working in Imam Khomeini Hospital in Songor, Kermanshah Province, Iran, in the first half of 2020 were randomly selected and divided into three groups (n=15 each). The first group participated in twelve 90-minute training sessions of cognitive-behavioral therapy (two sessions per week), and the second group took part in twelve 90-minute training sessions of emotion regulation therapy (two sessions weekly). However, the control group did not receive any treatment. The results were analyzed using multivariate analysis of covariance. Results: The results showed that the effectiveness of cognitive-behavioral therapy and emotion regulation therapy on the dependent variables of aggression (P=0.04), job stress (P=0.03), and general health (P=0.01) was significant. Pairwise comparison of the groups for dependent variables indicated that regarding the aggression variable, emotion regulation therapy based on was more effective (P=0.01), and considering the job stress variable, cognitive-behavioral therapy was more effective (P=0.04). It was also revealed that cognitive-behavioral therapy and emotion regulation therapy had the same effect on the general health of nurses (P=0.08). Conclusion: According to the obtained results, health officials should pay more attention to the mental health of nurses and, by considering both treatments, provide the ground to increase cognition and promote excitement in nurses.